2005
DOI: 10.1038/sj.mp.4001664
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of the COMT (Val158/108 Met) gene and schizophrenia: a meta-analysis of case–control studies

Abstract: There is strong evidence for a genetic contribution to schizophrenia, but the contribution of individual candidate genes remains uncertain. We attempted to replicate a recent metaanalysis that reported an association of the catechol O-methyltransferase (COMT) Val allele with schizophrenia, and suggested that this effect may be moderated by ancestry. We included reports published subsequent to the original meta-analysis, and included a formal test of the moderating effect of ancestry in order to test whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
133
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 28 publications
14
133
3
Order By: Relevance
“…The results suggest that the COMT functional allele is not a major factor in expression of schizophrenia in 22q11DS, similar to findings for schizophrenia in the general population (Glatt et al 2003;Munafo et al 2005). We must look elsewhere for major risk factors for schizophrenia.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results suggest that the COMT functional allele is not a major factor in expression of schizophrenia in 22q11DS, similar to findings for schizophrenia in the general population (Glatt et al 2003;Munafo et al 2005). We must look elsewhere for major risk factors for schizophrenia.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have found the COMT Met allele to be more common than the Val allele in severe forms of schizophrenia (Bilder et al 2004), yet there is an overall trend for association of the COMT Val allele with schizophrenia (Glatt et al 2003). The disparate results may be partly due to the etiologic heterogeneity of schizophrenia (Strous et al 2006), which could also account for the small effect sizes observed in association studies (Glatt et al 2003;Munafo et al 2005). …”
mentioning
confidence: 60%
“…Nevertheless, two other studies did not report a significant contribution of the Val 158 Met polymorphism of the COMT gene to schizophrenia and concluded that either the Val allele is in linkage disequilibrium (LD) with a nearby causal marker or the results differ when ethnically different populations are considered or the risk conferred by the Val allele is extremely low. 12,13 Results have also been obtained that suggest an eventual influence of this polymorphism in the response of schizophrenic patients to typical 14 and atypical 15 neuroleptics.…”
Section: Introductionmentioning
confidence: 89%
“…4 However, recent meta-analyses have questioned the association between schizophrenia and the COMT Val 158 Met polymorphism. [15][16][17] Impaired performance on the WCST has long been of interest in schizophrenia because WCST failure is associated with 'hypofrontality', that is a failure to activate the PFC. 6 More recently, WCST performance has attracted considerable interest as a potential endophenotype of schizophrenia, because it shows considerable heritability 18 and is impaired in the healthy relatives of patients with schizophrenia compared with unrelated controls.…”
Section: Introductionmentioning
confidence: 99%